Faces and Eyes in Human Lateral Prefrontal Cortex - Chan, Annie W.- Y.; Downing, Paul E. (Frontiers in Human Neuroscience, 2011)
Much of the work on face-selective neural activity has focused on posterior, ventral areas of the human and non-human primate brain. However, electrophysiological and fMRI studies have identified face responses in the prefrontal cortex. Here we used fMRI to characterize these responses in the human prefrontal cortex compared with face-selectivity in posterior ventral region. We examined a region at the junction of the right inferior frontal sulcus and the precentral sulcus (right inferior frontal junction or rIFJ) that responds more to faces than to several other object categories. We find that the rIFJ and the right fusiform face area (rFFA) are broadly similar in their responses to whole faces, headless bodies, tools, and scenes. Strikingly, however, while the rFFA preferentially responds to the whole face, the rIFJ response to faces appears to be driven primarily by the eyes. This dissociation provides clues to the functional role of the rIFJ face response. We speculate on this role with reference to emotion perception, gaze perception, and to behavioural relevance more generally.